PENDIDIKAN KESEHATAN TENTANG HYGIENE BERPENGARUH TERHADAP PERILAKU ORANG TUA DALAM MELAKUKAN HYGIENE PADA ANAK DIARE - Budhi Mustika, I Made; Susanti, Dwi; Badi’ah, Atik (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: The occurrence of diarrhea in children is correlated with parents’ practices on hygiene (hand- washing) behavior. The results of preliminary studies at Pediatric Ward Wonosari General Hospital indicated that most parents have lack of knowledge on the correct procedure of hand washing. Objectives: The aim of this research was to determine the effect of health education about hygiene on parents' behavior in performing hygiene in children with diarrhea in Pediatric Ward Wonosari General Hospital. Methods: This research was quasi experimental with one group pre-test and post-test design. Research was conducted at Pediatric Ward in Wonosari General Hospitalin 2012. Fifty-six respondents were recruited through saturated sampling. Data were analyse during apaired t-test with significance level of α<0.05. Results: Parents’ behavior in performing hygiene at the time of pretest was in majority was less (with a score of≤ 56%) of 51 respondents (91.1%), this score increased with majority was good (with a score of 75-100%) of 50 respondents (89.3%) in post-test. Paired t-test resulted in p-value=0.000 (p <0.05). Conclusion: There was a significant effect of health education about hygiene on parents’ behavior in performing hygiene in child with diarrhea in Pediatric Ward Wonosari General Hospital. Keywords: Behavior, Health Education, Hygiene